Fasciitis of the lower leg after COVID-19 vaccination. (2022) - Ide, Satoshi; Kurozumi, Atsumasa; Takeshige, Akiko; Shimomura, Akira; Watanabe, Riri; Inagaki, Takeshi
Highlights: The occurrence of fasciitis after COVID-19 vaccination is rare. The BNT162b2 COVID-19 vaccine can cause fasciitis distant to the injection site. The use of steroids is not essential for treatment of vaccine-associated fasciitis.